(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article views eight ways of self-actualization of A. Maslow as exemplified by poetic work of Y. Levitanskij. The author arrives at the conclusion that Y.Levitaskij may be considered a self-actualized person.